Current Cancer Treatment - Rajer, Mirjana; Segelov, Eva (IntechOpen, 2020)
This book is a collection of in-depth chapters on many aspects of contemporary cancer treatment. Written by experts worldwide, each chapter provides a detailed summary of the state-of-the art knowledge in the area, with extensive references and clear and informative diagrams. The volume is divided into two sections: "Basic Science" and "Clinical Challenges." The five chapters in the first section cover MicroRNA, the role of angiogenesis in the tumor microenvironment, microbial metabolites in the gastrointestinal microenvironment, the role of dendritic cells in anti-tumor immunity, and challenges of current cancer biomarkers. The two chapters in the second section cover pediatric CNS tumors and the role of sentinel node biopsy in endometrial cancer. The information in this book is designed for cancer clinicians and interested readers to whom this knowledge is important for focusing research and improving patient outcomes.